2022
DOI: 10.3390/ijms23137452
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Is a Proinflammatory Stimulus of Renal Tubular Epithelial Cells

Abstract: Chronic kidney disease (CKD) refers to a spectrum of diseases defined by renal fibrosis, permanent alterations in kidney structure, and low glomerular-filtration rate. Prolonged epithelial-tubular damage involves a series of changes that eventually lead to CKD, highlighting the importance of tubular epithelial cells in this process. Lysophosphatidic acid (LPA) is a bioactive lipid that signals mainly through its six cognate LPA receptors and is implicated in several chronic inflammatory pathological conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 159 publications
0
2
0
Order By: Relevance
“…Moreover, LPA induced the phosphorylation of transcription factors JUN and CREB1 and signaling proteins IκBα and MEK1. Our results suggested that the JNK/c-JUN, MEK/ERK, NFκB, and CREB pathways are implicated in the production of some of the LPA-mediated secreted factors [24]. Furthermore, upon clustering of the 176 stimuli, LPA clustered with proinflammatory molecules such as IL-1α, IL-1β, IL-17α, TNFα and others, attributing to LPA a proinflammatory role.…”
Section: Pathophysiologymentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, LPA induced the phosphorylation of transcription factors JUN and CREB1 and signaling proteins IκBα and MEK1. Our results suggested that the JNK/c-JUN, MEK/ERK, NFκB, and CREB pathways are implicated in the production of some of the LPA-mediated secreted factors [24]. Furthermore, upon clustering of the 176 stimuli, LPA clustered with proinflammatory molecules such as IL-1α, IL-1β, IL-17α, TNFα and others, attributing to LPA a proinflammatory role.…”
Section: Pathophysiologymentioning
confidence: 71%
“…These cells were exposed to LPA and 175 other inflammatory-immunological stimuli, and multiplex ELISA was performed. LPA was found to induce the secretion of CCL2, also known as monocyte chemoattractant protein 1 (MCP-1), CCL3, also known as macrophage inflammatory protein-1α (MIP-1α), IL-6, IL-8, CXCL10 and soluble ICAM1 [24]. Moreover, LPA induced the phosphorylation of transcription factors JUN and CREB1 and signaling proteins IκBα and MEK1.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Examples of such transactivation are, for instance, LPAR-dependent G-protein activation of Src kinase, which then phosphorylates EGFR, or LPAR-based activation of the MAPK pathway, which in turn leads to production of heparinbinding EGF-like growth factor, which again activates EGFR, leading to activation of transcription factors, including those mentioned above (Umata et al, 2001;Shah et al, 2005;Liu et al, 2009a). The transcription factors then elicit expression of pro-inflammatory cytokines such as CCL2, CCL3, CXCL10, ICAM1, IL-6, and IL-8 by the target cells (Magkrioti et al, 2022).…”
Section: Atx and Inflammationmentioning
confidence: 99%
“…LPA exerts its function through speci c membrane receptors (LPARs), involved in several mechanisms, such as platelets aggregation, vascular tone control, in ammation, endothelial dysfunction, and neuropathic pain; among others [12][13][14]. As mentioned, the ATX-LPA axis has been described to modulate different processes that are involved in the development and evolution of migraines, such as vascular tone [15,16], in ammation [17,18], neuroin ammation [19], and neuronal excitation [20], and pain [21,22]. However, its implication in migraine has not been studied.…”
Section: Introductionmentioning
confidence: 99%